The prevalence of occupational-related low back pain among working populations in sub-saharan Africa: a systematic review and meta-analysis - Atalay, Yibeltal Assefa; Gebeyehu, Natnael Atnafu; Gelaw, Kelemu Abebe (My University, 2024)
Work-related musculoskeletal disorders represent a major public health problem, contributing significantly to the global burden of disability-adjusted life years and affecting the quality of life of all population groups. The main problem in most musculoskeletal disorders is low back pain. Therefore, our study aims to identify the overall prevalence of work-related low back pain among the working population in sub-Saharan Africa. Research published between 2010 and 2023 in English, conducted in Sub-Saharan Africa was included in this systematic review and meta-analysis. Using Boolean logic operators and targeted keywords, we searched for publications on a number of electronic databases (Web of Science, PubMed, Google Scholar, African Journals Online (AJOL), and Science Direct). The Joanna Briggs Institute Critical Appraisal techniques were utilized to conduct a quality assessment of the papers and ascertain their relevance to the study. The degree of heterogeneity among the included studies, the 95% confidence interval, and the pooled prevalence were estimated using a random effects model. Sensitivity studies were carried out to determine the causes of heterogeneity and the impact of outliers. In this study, a total of 970 articles were retrieved, and 35 studies were included in the systematic review and meta-analysis. The overall estimated pooled prevalence of low back pain among the working population in sub-Saharan Africa was (55.05% [95% CI: 49.34, 60.76]). Based on a sub-group analysis by countries, the higher pooled prevalence of low back pain was found in Uganda at (61.48% [95% CI: 40.39, 82.57]), while the lower pooled prevalence of low back pain was in Ghana at (34.48% [95% CI: 17.96, 51.01]). This systematic review and meta-analysis found that 55.05% of the included study participants experienced low back pain in the previous years. Therefore, it is recommended that policymakers incorporate and enhance strategies for the prevention and management of low back pain within the health system management guidelines of each country.